[OP.5B.01] QUANTIFICATION OF HEART RATE DEPENDENCY OF AORTIC PULSE WAVE VELOCITY. (September 2016) - Tan, I.; Spronck, B.; Delhaas, T.; Reesink, K.; Kiat, H.; Barin, E.; Butlin, M.; Avolio, A.
Abstract : Objective: Aortic stiffness, as measured by carotid-femoral pulse wave velocity (cfPWV), is an independent marker for cardiovascular morbidity and mortality, but is dependent on blood pressure (BP) and possibly heart rate (HR). Acute HR changes are often accompanied by increased BP. This presents the need to quantify the BP-independent effect of HR on cfPWV. Design and method: Individuals (n = 52, age 40–93 years, 11 female) with in situ cardiac pacemakers were paced at 60, 70, 80, 90 and 100 bpm with BP and cfPWV measured at each pacing step. Influence of BP was corrected by 3 different methods: (1) statistically, by including both HR and mean arterial pressure (MAP) in a multivariate mixed model; (2) mathematically, using an exponential relationship between aortic BP and cross-sectional lumen area; (3) correcting for BP changes using measured BP dependency of cfPWV derived from systemic and hydrostatic changes in BP induced by a change in position (seated and supine) in a subset (n = 17) of the subjects; this correction method assumed a linear relationship between MAP and cfPWV. The mathematical model was parameterised for each subject using cfPWV at 60 bpm to predict the effect of measured BP fluctuations on cfPWV at HRs 70 to 100 bpm; the BP-independent effect of HR on cfPWV was quantified by comparing measured to predicted cfPWV. Results: HR increases were not only significantly associated with increased cfPWV (0.32[0.27–0.37] m/s/10 bpm, mean [95%CI]), but also with MAP (3.6[3.2–4.1] mmHg/10 bpm). Corrected BP-independent effects of HR on cfPWV were quantified as 0.19[0.10–0.27] m/s/10 bpm using method (1), 0.17[0.11–0.23] m/s/10 bpm using method (2), and 0.17[0.12–0.23] m/s/10 bpm using method (3). The averaged HR-dependency of cfPWV of the three methods was 0.18 m/s/10 bpm. Conclusions: Elevation of HR with pacing increases BP. This BP change can be corrected for by using multiple methods to calculate the HR dependency of cfPWV. The significant dependency of cfPWV on HR, independent of BP, is in the range of 0.17 to 0.19 m/s/10 bpm. Further work is required to investigate if this dependency changes with age or gender.